The Relationship between Family Burden and Coping Strategies in the Caregiver of Patient with Schizophrenia in Community - Suharsono; C., R. Marchira; I. , Rahmat; Subandi (International Journal of Psychosocial Rehabilitation, 2020)
Schiz1ophrenia is a severe mental disorder that placed considerable burden on the caregivers. The family experienced a lot of physical, emotional, and financial distress due to a patient’s abnormal behavior. Family caregivers of schizophrenia patients face a variety of challenges that have a significant impact on mental health and physical health. The complexity faced by family caregivers requires skill in overcoming the burden experienced, also known as a coping strategy. Individuals who more often use problem-focused coping are more able to deal with stress situations compared with the use of emotion-focused coping that improves the quality of life. By understanding the relationship between caregivers burden and coping strategies of the caregiver family, it will have a positive impact on the clinical outcome of schizophrenic patients. Therefore, it becomes important to examine the relationship between caregiver burden and coping strategies in the caregiver family of schizophrenic patients. Objective To know the relationship between family burden and coping strategy among family caregiver of patient with schizophrenia in community. This was an observational analytic study (non-experimental) with a cross-sectional design. The subject of this study was 100 family caregiver of patients with schizophrenia in the community Special Region of Magelang District, Central Java. Caregiver Burden was assessed by using Zarit Burden Interview (ZBI) and Coping strategies were assessed with the Indonesian version of the Family Coping Questionnaire (FCQ) instrument which was previously tested for validity and reliability by the researchers.. Statistical analysis was performed with Pearson correlation test. The significance level of the statistical test was defined at p<0.05. The results of this study show that the majority of participant are female and have been caring more than 5 year. The study showed that 20% of the family caregivers reported having a severe level of burden, and the majority (44%) reported having moderate level of burden and 36 % reported having mild level of burden. The bivariate analysis showed a significant relationship between family burden and family coping (r = 0.0951, p = 0.006). There is a significant correlation between family burden with coping strategy in family caregiver of schizophrenia patient at community Special Region of Magelang, Central Java.